(untitled) (Journal of Science & Technology, 2020)
Lean manufacturing principles have emerged as a cornerstone in modern production systems, emphasising efficiency, waste reduction, and continuous improvement. This review article conducts a comprehensive meta-analytical assessment of the application and impact of lean manufacturing principles across diverse industries. By synthesising findings from various studies, this review aims to provide a holistic understanding of the effectiveness of lean practices in achieving optimal efficiency within manufacturing processes.